2019
DOI: 10.1108/tldr-12-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Community services and transforming care: reflections and considerations

Abstract: Community services and transforming care 1 Community services and transforming care: reflections and considerations Abstract Purpose -The purpose of this paper is to consider the existing evidence base regarding community services for people with learning disabilities in the context of Transforming Care (TC). Design/methodology/approach -Reflections and commentary on the provision of community services for people with learning disabilities following Washington et al.'s article on admissions and discharges from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Underpinning these poor outcomes are the lack of well-defined care pathways for within the National Institute for Health and Care Excellence (NICE) guidelines, further complicated by legal restrictions imposed by the MoJ, and the limited capacity and capability of health and social care providers in the community (Barnoux, 2019;Washington et al, 2019). However, there is agreement that a diagnosis of autism alone does not predict treatment outcome (Esan et al, 2015) but rather a range of other factors which require careful consideration in the assessment of risk, interventions, and opportunities for leave and/or discharge from hospital.…”
Section: Stay In Hospitalmentioning
confidence: 99%
“…Underpinning these poor outcomes are the lack of well-defined care pathways for within the National Institute for Health and Care Excellence (NICE) guidelines, further complicated by legal restrictions imposed by the MoJ, and the limited capacity and capability of health and social care providers in the community (Barnoux, 2019;Washington et al, 2019). However, there is agreement that a diagnosis of autism alone does not predict treatment outcome (Esan et al, 2015) but rather a range of other factors which require careful consideration in the assessment of risk, interventions, and opportunities for leave and/or discharge from hospital.…”
Section: Stay In Hospitalmentioning
confidence: 99%
“…It is now acknowledged that the complexity and scale of the challenge was underestimated, and the scope and quality of data on inpatients with ID was poor (National Audit Office, 2015). A number of reasons have been suggested for the failure to reduce hospital placements within the forensic cohort, including ongoing needs relating to forensic risk (Alexander et al, 2015;Chester et al, 2017), and a lack of specialised community service provision (Barnoux, 2019;Washington et al, 2019). One of the most significant drivers for continued use of inpatient ID services is mental ill health.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis indicated that in 51% of the admissions there were delayed community transitions; with 83% of these delays reflecting a lack of community-based provision. In addition, Barnoux (2019) reflected on the difficulties incumbent on community intellectual disability teams in dealing with an increasingly complex population. These include an absence of good practice guidelines, lack of adequate supervision, excessive caseloads and poor staffing numbers.…”
mentioning
confidence: 99%